Examining of the Attachment Style to Parents, Depression Levels, and Stress Management Styles of Private Soldiers in terms of Substance Abuse - Koçhan, Kemal; İlhan, Tahsin (Addicta: The Turkish Journal on Addictions, 2015)
This study compares parental attachment, coping strategies, and depression scores of soldiers and recruits who use substances with those who do not. Furthermore, we also explore reasons for substance use of the soldiers and recruits and how their parental attachment, coping strategies, and depression scores differentiate by the absence and severity of the addiction. The study group comprised 200 soldiers and recruits (all of them were male) who served in a Turkish Infantry Training Brigade Command in 2014, of whom 100 were substance abusers and 100 were not. The age of the participants ranged from 20 to 32 (X= 21.69, SD = 2.38). The Personal Information Form, the Addiction Profile Index Questionnaire, the Parental Bonding Instrument, the Coping Strategies Inventory Short-Form, and the Depression Anxiety Stress Scale were used for data collection. The data were analyzed using a frequency analysis, t-test, and one-way Analysis of Variance (ANOVA). The study results showed that parental attachment, coping strategies, and depression scores of substance abusers differed significantly compared to the scores of non-abusers. Furthermore, a significant number of substance abusers indicated that the attitudes and problems within the family were main reasons for starting to abuse substances.